PARTIAL CHARACTERIZATION of lipase from COCOA BEANS (Theobroma cacao. L.) of clone PBC 159 - Ratna Agung Samsumaharto (Indonesian Journal of Chemistry, 2008)
A study was carried out to characterize the cocoa lipase from cocoa beans (Theobroma cacao, L.) of clone PBC 159. The optimum temperature of cocoa lipase was 30-40 °C and the pH optimum was 7.0-8.0. The moleculer weight of the lipase enzyme was in between 45-66 kDa. The results indicate that Km value for cocoa bean lipase was 2.63 mM, when trimyristin was used as a substrate. The incubation of cocoa bean lipase with triolein and tributyrin (as substrate) yielded Km of 11.24 and 35.71 mM, respectively. The Vmax value obtained from the incubation of the lipase with a wide range of substrates, including tributyrin, trimyristin and triolein, are expressed as µmole acid/min/mg protein for cocoa lipase. Vmax values decreased with the increase in the triacylglycerol chain-length, with Vmax values of 27.78, 13.16 and 11.63 µmole acid/min/mg protein when incubated with tributyrin, trimyristin and triolein, respectively. Inhibition of lipase occurred in the presence of diisopropyl flourophosphate, N-bromosuccinimide and 5,5-dithiobis-(-2-nitrobenzoic acid).